Socio-cultural and gender perspectives in John 7:53-8:11 : exegetical reflections in the context of violence against women in Zambia - Lungu, James (Stellenbosch : Stellenbosch University, 2016)
Thesis (MTh)--Stellenbosch University, 2016.